Aplicações de equações diferenciais ordinárias em circuitos elétricos RL e RLC - Correa, Florene Nazario (2022)
This academic work presents a study involving applications of Ordinary Differential Equations (ODE) related to the Electric Circuits area, specifically in resistor-inductor (RL) and resistor-inductor-capacitor (RLC) circuits. The applications approached involve Ordinary Differential Equations of first and second order that describe the behavior of these electrical circuits. The great relevance of ODEs is mainly in relation to their applications, due to the fact that the investigation of many problems can be reduced to the solution of such equations. This study has as theoretical support the historical context, definitions and chosen methods of ODEs as well as basic circuit concepts. Finally, we present some applications in circuit problems, solving the resulting ODE from the known data of the investigated problem. However, these differential equations are an important mathematical tool because they allow to describe processes, model and solve problems, as well as the understanding and analysis of phenomena and problems. Keywords: ODE. Applications. Electric Circuits.